Using Landsat satellite imagery for assessment and monitoring of long-term forest cover changes in Dak Nong province, Vietnam - Thien, Bui Bao; Phuong, Vu Thi (Geographica Pannonica, 2023)
Forests are essential in regulating climate and protecting land resources from natural disasters. In Vietnam’s Dak Nong province, forest cover has changed significantly between 1989 and 2021. This study applies remote sensing and geographic information systems (GIS) approaches to detect negative changes in forest cover as well as other land cover types. The maximum likelihood classification tool was used to classify Landsat images for the years 1989, 2001, 2011, and 2021, with post-classification accuracy evaluated through kappa coefficient statistics. The potential to based classification on Normalized Difference Vegetation Index (NDVI) and Soil Adjusted Vegetation Index (SAVI) to detect changes in forest cover compared with supervised classification was also evaluated. The land use and land cover change detection results show that the forest area decreased from 77.54% of the study area in 1989 to 33.97% in 2021, with a total forest loss of 2,953.48 km2 and only 117.12 km2 of newly planted forest during this period. Broadly, forest cover in the area has been severely reduced, often due to indiscriminate logging and expansion of agricultural land on the forest edge.
Keywords: Forest cover; Forest loss; Landsat; Vegetation Index; Remote sensing; Vietnam